Which indicator should be used? A comparison between the incidence and intensity of catastrophic health expenditure: using difference-in-difference analysis - Jun Hyuk Koo; Hyun Woo Jung (Health Economics Review, 2022)
Background: Catastrophic health expenditure (CHE) represents out-of-pocket payment as a share of household income. Most previous studies have focused on incidence aspects when assessing health policy efects. However, because CHE incidence is a binary variable, the efect of the health policy could not accurately be evaluated. On the contrary, the intensity of CHE is a continuous variable that can yield completely diferent results from previous studies. This study reassesses the coverage expansion plan for four serious diseases using the intensity of CHE in Korea. Methods: We used the Korea Health Panel Study from 2013 to 2015 to conduct the analysis. The study population is households with chronic diseases patients. We divided the population into two groups: the policy benefciary group, i.e., households with a patient of any of the four serious diseases, and the non-benefciary group. A diference-indiference model was employed to compare the variation in the intensity and incidence of CHE between the two groups. We defned the incidence of CHE as when the ratio of out-of-pocket medical expenses to household income is more than a threshold of 10%, and the intensity of CHE is the height of the ratio subtracting the threshold 10%. Results: The increased rate of CHE intensity in households with four serious diseases was lower than that in households with other chronic diseases. The interaction term, which represents the efect of the policy, has a signifcant impact on the intensity but not on the incidence of CHE. Conclusions: CHE indicators should be applied diferently according to the purpose of policy evaluation. The incidence of CHE should be used as the fnal achievement indicator, and the intensity of CHE should be used as the process indicator. Furthermore, because CHE has an inherent characteristic that is measured by the ratio of household income to medical expenses, to lower this, a diferential out-of-pocket maximum policy for each income class is more appropriate than a policy for strengthening the coverage for specifc diseases.
Keywords: 330; Catastrophic health expenditure; Health policy; Out-of-pocket medical expenditures; Diference-indiference analysis; Propensity score matching